2007
DOI: 10.1128/aac.00954-06
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility and Synergy Studies of Burkholderia cepacia Complex Isolated from Patients with Cystic Fibrosis

Abstract: Susceptibility (18 antimicrobial agents including high-dose tobramycin) and checkerboard synergy (23 combinations) studies were performed for 2,621 strains of Burkholderia cepacia complex isolated from 1,257 cystic fibrosis patients. Minocycline, meropenem, and ceftazidime were the most active, inhibiting 38%, 26%, and 23% of strains, respectively. Synergy was rarely noted (range, 1% to 15% of strains per antibiotic combination).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 29 publications
5
76
1
1
Order By: Relevance
“…the sensitivity to ceftazidim and piperacilin varied (10). About 95% of the clinic isolates of B. cepacia were susceptible to sulphometoxazol/trimetoprim, 85% to chloramphenicol, 80% to piperacillin, and 65% to doxycyclin and ceftazidim (32). Some of our results confirmed the data obtained by other authors.…”
Section: Fig 3 Morphological Types Of Coloniessupporting
confidence: 82%
“…the sensitivity to ceftazidim and piperacilin varied (10). About 95% of the clinic isolates of B. cepacia were susceptible to sulphometoxazol/trimetoprim, 85% to chloramphenicol, 80% to piperacillin, and 65% to doxycyclin and ceftazidim (32). Some of our results confirmed the data obtained by other authors.…”
Section: Fig 3 Morphological Types Of Coloniessupporting
confidence: 82%
“…Another important CF pathogen, Burkholderia cepacia, was evaluated by the same group using checkerboard testing. Of 2,621 strains from 1,257 patients, synergy was only identified in 1 to 15% of strains (23). Aaron and colleagues tested a different subset of Burkholderia cepacia isolates using the MCBT method and found that triple antimicrobial combinations were bactericidal in 81 to 93% of isolates, which was superior to double antimicrobial combinations (7).…”
Section: Cystic Fibrosis and Synergy Testingmentioning
confidence: 99%
“…Nevertheless, the most suitable AST method of isolates obtained from CF patients is increasingly under debate. Beyond methodological discrepancies the poor correlation of in vitro data and the outcome of the patients is disappointing, irrespective of the testing of single antibiotics or antibiotic combinations [41][42][43]. This seems to be not surprisingly, since (i) the definition of resistance deduced from in vitro testing of bacteria and discrete clinical breakpoints is directed in particular towards the treatment of acute infections and does not equally fit to the situation of chronic infections (ii) in CF only a few possibly representative isolates were tested and (iii) rather all in vitro methods are inappropriate to mimic the complex environment of the CF lung comprising various sputum components, high bacterial densities, biofilm growth, anaerobiosis and the coexistence of different species or phenotypic variants.…”
Section: Columbia Colistin-nalidixic Acid Agar Lipase-salt-mannitol mentioning
confidence: 99%